O processo de luto na interrupção de gestação por feto anencéfalo - Carmo, Jorge Ramalho do (2008)
In the process of disenfranchised loss there is little or no opportunity for public expression to facilitate the mourning process, with few chances of sharing the grief of the loss openly. The fetal pathologies incompatible with life outside the womb are losses that happen during pregnancy or shortly after birth and it is not considered socially significant because it is as if the mother had no time to develop bond with the baby. This study aimed to examine and understand the process of grief through a case study related to the interruption of a anencephalic fetus pregnancy, identifying characteristics and peculiarities as the issue of religion and the family and social support at this kind of loss. It was conducted at Hospital Municipal de Sabóya Arthur Ribeiro, known as Jabaquara Hospital in Sao Paulo. The participant was a woman who had interrupted the pregnancy of a anencephalic fetus, and was submitted to an interview based on a semi-structured guide. Information was discussed through analysis of its content and the process of mourning was characterized from the peculiarity of the loss by lethal fetal abnormality and interruption of pregnancy. It was observed that the gestation s history characteristics influence the development of the process of mourning. The difficulties of healthcare professionals in dealing with patients in this situation were also observed. There is a gap of support between the diagnosis and the period of hospitalization that leaves the woman without guidance and emotional support in such difficult loss. The symptoms of unrecognized mourning are intensified depending of family s type of support that can be offered and also the religious support for these specific cases of pregnancy s interruption. Finishing this study is the possibility to understand the lacks of assistance to these women, concerning to the disenfranchised loss process. The determinant factors in Brazilian reality concerning to the mourning process include the religious support, the attitude of healthcare professionals from reference services, the family s support and personal structure. Reflect about these topics is an opportunity to think about the quality of care to these women and the continual support to the mourning process